1967
DOI: 10.1002/ar.1091570204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single dose of anti‐LH‐serum at proestrus on the rat estrous cycle

Abstract: Previous studies have shown that pentobarbital administration at 2 P.M. of proestrus i n the rat blocks ovulation and the drop in pituitary LH content normally seen at estrus; these data were interpreted as indicating that the drug acted by blocking LH release. Signs of prolongation of estrogen secretion were seen in these rats and, in the absence of further treatment, ovulation occurred 24 hours later. In the present study a single dose of anti-ovine-LH-serum administered at 1 P.M. of proestrus also blocked o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It is possible that barbiturates administered on the day before proestrus exert a partial blockade of LH release, thus reducing estrogen and progesterone secretion enough to prevent the triggering of the ovu latory surge of LH on the day of proestrus but not enough to prevent vaginal and uterine changes. (Following a single injection of anti-LI I serum at proestrus, uterine and vaginal signs of estrogen secretion returned more quickly in the next cycle than the LH release for ovu lation, suggesting that more steroid may be necessary to induce LH release than uterine and vaginal signs [Schwartz and Gold 1967]). Another possibility is that the barbiturates did not block estrogen secretion to any appreciable extent, but were blocking the gonado trophin release responsible for progesterone secretion, which may be necessary for release of the ovulatory surge of LH, when superimposed on a background of estrogen secretion [Everett and Sawyer 1949].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that barbiturates administered on the day before proestrus exert a partial blockade of LH release, thus reducing estrogen and progesterone secretion enough to prevent the triggering of the ovu latory surge of LH on the day of proestrus but not enough to prevent vaginal and uterine changes. (Following a single injection of anti-LI I serum at proestrus, uterine and vaginal signs of estrogen secretion returned more quickly in the next cycle than the LH release for ovu lation, suggesting that more steroid may be necessary to induce LH release than uterine and vaginal signs [Schwartz and Gold 1967]). Another possibility is that the barbiturates did not block estrogen secretion to any appreciable extent, but were blocking the gonado trophin release responsible for progesterone secretion, which may be necessary for release of the ovulatory surge of LH, when superimposed on a background of estrogen secretion [Everett and Sawyer 1949].…”
Section: Discussionmentioning
confidence: 98%
“…Some were laparotomized between 10 and 11a.m. on the following morning ("proestrus") to check the extent of uterine distention or ballooning, previous experi ments having shown that this procedure does not interfere with subsequent events leading to ovulation [Schwartz 1964;Schwartz and Gold 1967], At autopsy between 10 and 11 a.m. on the morning of expected cstrus, oviducts were inspected under the dissecting microscope for the distended, translucent area indicative of recent ovulation. In many of the obviously positive cases this ampullar segment was cut and ova were extruded and counted, or serial sections of one ovary and oviduct were prepared; in every negative or questionable case such serial sections were made.…”
Section: Methodsmentioning
confidence: 99%
“…While FSH has been shown to bring about ovulation in hypophysectomized, pentobarbital-or chlorpromazine-blocked rats and in PMSG-primed immature rats (Carter et al, 1961 ;Lostroh & Johnson, 1966;Harrington, Bex, Elton & Roach, 1970;Nuti, McShan & Meyer, 1974;Tsafriri et al, 1976), endogenous FSH has not been found necessary for ovulation in any studies, including the present, in which FSH antiserum was used (Schwartz, Krone, Talley & Ely, 1973;Moudgal, Rao, Maneckjee, Muralidhar, Mukku & Sheela Rani, 1974;Jagannadha Rao et al, 1974a;Schwartz, Cobbs, Talley & Ely, 1975). The role of LH in ovulation, on the other hand, has been unequivocally demonstrated in many systems (Kelly, Robertson & Stanfield, 1963;Lostroh & Johnson, 1966;Schwartz & Gold, 1967;Sasamoto, 1969;Madhwa Raj & Moudgal, 1970;Ely & Schwartz, 1971;Moudgal, MacDonald & Greep, 1971;Jagannadha Rao et al, 1974a;Lipner et al, 1974;Schwartz et al, 1975;Tsafriri et al, 1976). It is probable that in systems in which ovulation has been induced by FSH, it is due to synergism with the minimal amounts of LH that may be found in the system (either present in the system ia low amounts, even after hypophysectomy, or as a contaminant), because FSH in combination with minimal amounts of LH has been shown to cause ovulation in hypophysectomized immature rats (Lipner et al, 1974).…”
Section: Discussionmentioning
confidence: 60%
“…This was true except when lh antiserum was given on Days 1 to 5 in intact rats, indicating that antibodies can exist for several days in circulation (Quadri et al, 1966;Schwartz & (Finn, 1965). Hetherington (1968) demonstrated a difference in decidua formation following an intra-uterine injection of air compared with oil.…”
Section: Discussionmentioning
confidence: 99%